Examining the Application of Mobile Phone in Business Practice Among Small Scale Businesses in Tamale Metropolis - ABUBAKARI, ABDUL-RAZAK (Discoveries in Agriculture and Food Sciences, 2020)
This research examined the application of mobile phone in business practice among small scale businesses in Tamale metropolis. A quantitative research approach was adopted and the target population was users of mobile money application among Small Scale Businesses in Tamale Metropolis. The general objective of the study is to examining the application of mobile phones in business practice among Small Scale Businesses in Tamale metropolis. It is found out by the researcher that usually people use it to transact business that is making and receiving money as payment. Hence, it is established that mobile phone gives them opportunity to keep records as evidence. The research revealed that, mobile money is noted to facilitate and speed up transaction of businesses. Also, it is found out that, it enhances convenience of handling resources effectively. It is established that, monies in the mobile phone are safer and remain safe even if the mobile device is lost. It is clearly indicated that many people lose their monies every now and then from fraudsters through the introduction of mobile money. The study shows that technological changes are some of the factors Small Scale Businesses faced. To optimize the benefits to be realized from mobile money application in businesses, there is the need to overcome the challenges of the application among small scale businesses.